ANALISIS SEMIOTIKA RIFFATERRE TERHADAP LAGU ATUNA TUFULI KARYA REMI BANDALI - Muhammad Nurfaizi Yuhmansyah; Sitti Wahidah Masnani; Haeruddin Haeruddin; Andi Agussalim; Mujadilah Nur (Universitas Islam Negeri Sumatera Utara Medan, 2024)
Songs are a form of oral literature capable of conveying messages through language and music. This study analyzes the meaning of the lyrics in Atuna Tufuli, popularized by Shirine, using Michael Riffaterre's semiotic theory of poetry. The research aims to uncover meaning through four key elements: displacing, distorting, and creating meaning; heuristic and hermeneutic reading; matrix; and model and hypogram. This descriptive-qualitative research employs a library study approach. The findings show that the lyrics convey complex expressions of love and longing through indirect expression. Heuristic and hermeneutic readings reveal restrained emotional expressions. The matrix emphasizes the desire of children in conflict areas to live in peace and freedom. The model and hypogram indicate intertextual connections with universal themes of longing for a normal childhood and peace-elements also found in classical Arabic poetry. These recurring themes evoke empathy and reflect a broader call for attention to children affected by war and violence.